Dynamical Multimodality in Systems Driven by Ornstein–Uhlenbeck Noise - Mandrysz, Michał; Dybiec, Bartłomiej (Entropy (Basel, Switzerland), 2025)
The properties of dynamical systems driven by noise are determined by the combined action of deterministic forces and random fluctuations. The action of non-white (correlated) noise is capable of producing stationary states with a number of modes larger than the number of (stable) fixed points of the deterministic potential. In particular, the action of Ornstein–Uhlenbeck noise can induce the bimodality of the stationary states in fixed single-well potentials. Here, we study the emergence of dynamical multimodality in systems subject to the simultaneous action of Ornstein–Uhlenbeck and Markovian dichotomous noise in 1D and 2D setups. The randomization of the potential due to the action of dichotomous noise can be used to control the number of modes in the stationary states.